PELATIHAN BUSINESS ENGLISH BAGI SISWA SMK JAYAWISATA 1 JAKARTA PUSAT - Siti Ithriyah; Veronika Yuni T; Nurmawati Nurmawati (PT. Jurnal Center Indonesia Publisher, 2024)
Learning English is fundamental and speaking English is a requirement that appears in every job vacancy. In vocational school vocational students' learning, every student should be able to understand English, especially if they take a tourism or hospitality vocation. Therefore, UHAMKA and Jayabaya University lecturers held community service activities (PKM) at SMK Jayawisata 1 Central Jakarta with the aim of identifying English language needs for vocational school students. This PKM is held in the form of providing materials and training in English role studies, with the aim of increasing knowledge in business management, e-commerce and career planning. The method used in this study is through a literature study which collects several previous studies to answer the role of English. Use of English and the influence of using English for the purpose of applying knowledge regarding business management, e-commerce and career planning. It is hoped that all SMK Jayawisata 1 students who have taken part in training in the lecturer's role, namely PKM (Community Service), can broaden their knowledge of Business English. Based on the results of this literature study, it can be concluded that English plays an important role as a communication tool for business purposes.